Sonographic Evaluation of the Endotracheal Tube Position in the Neonatal Population: A Comprehensive Review and Meta-Analysis - Congedi, Sabrina; Savio, Federica; Auciello, Maria; Salvadori, Sabrina; Nardo, Daniel; Bonadies, Luca (Frontiers in Pediatrics, 2022)
Neonatal intubation is a challenging procedure, especially in preterm newborn, where endotracheal tube (ETT) position requires a high level of precision, given the shortness of the airways, and prompt confirmation. The current gold standard forETT verification is chest X-ray (CXR); however, this tool presents some limits, such as ionizing radiation exposure and delayed obtaining, that ultrasound could overcome.To evaluate ultrasound efficacy in determining ETTplacement adequacy in preterm and term newborns.To compare the time required for ultrasound confirmation vs time needed for other standard of care methods.A search in Medline, PubMed, Google Scholar and in the Cochrane Central Register of Controlled Trials (CENTRAL) was performed. Our most recent search was conducted in September 2021 including the following keywords: "newborn", “infant”,“neonate”,“endotracheal intubation”,“endotracheal tube”,“ultrasonography”,“ultrasound”.We considered randomized and quasi-randomized controlled trials, prospective and retrospective papers published after 2000, involving neonatal intensive care unit (NICU) population needing intubation/intubated infants and evaluating ultrasound efficacy and/or accuracy to detect ETT position versus a defined gold-standard method. Three review authors independently assessed studies quality and extracted data. We identified 14 eligible studies including a total of 602 ETT evaluations in NICU or in the delivery room. In about 80% of cases the gold standard for ETT position was CXR. Ultrasound was able to identify the presence of ETT in 96,8% of the evaluations, with a pooled ultrasound sensitivity of 91.48% (95% CI: 88.13 to 94.14%; p<0.005) in detecting the same ETT position of CXR. Bedside ultrasound confirmation was also found to be significantly faster compared to CXR obtaining.